2015
DOI: 10.1111/jbi.12595
|View full text |Cite
|
Sign up to set email alerts
|

Red Sea fishes in the Mediterranean Sea: a preliminary investigation of a biological invasion using DNA barcoding

Abstract: Aim More than 90 marine fish species in the Mediterranean have been determined to be alien species of Red Sea origin to date and therefore it is important to prioritize research into cataloguing their distribution and impacts. The aims of this study were to establish a barcode library for alien Mediterranean fishes of probable Red Sea origin and to initiate analyses of their invasion dynamics.Location Mediterranean Sea.Methods Specimens of exotic fishes were collected directly from the Mediterranean Sea off th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 64 publications
(82 reference statements)
2
73
0
Order By: Relevance
“…Based on the K2P distance matrix, the COI identification system may help define the limits of nucleotide divergence used to separate lineages (Hebert et al., ). The pairwise genetic distance matrix (Table ) showed considerable divergence between groups, varying from 5.2% to 25.0%, values that are consistent with divergence estimates in studies that have designated new fish species from comparisons with recognized taxa (Amaral et al., ; Baldwin, Cristina, & Lee, ; Bariche et al., ; Connell, Victor, & Randall, ; Guimarães‐Costa et al., ; Melo, Benine, Mariguela, & Oliveira, ; Oliveira et al., ; Tornabene et al., ; Van Tassell, Joyeux, Macieira, & Tornabene, ; Victor, Hanner, Shivji, Hyde, & Caldow, ). When the 2% species threshold for COI sequences (Hebert et al., ) is applied to the data analyzed in the present study, three of the 14 species sampled, Gobiomorus dormitor , Eleotris fusca and Dormitator maculatus , presented evidence of genetic structuring throughout their distribution in the Neotropical and Indo‐Pacific regions, based on nucleotide divergence values of 5.2%–13.1%, as well as reciprocal monophyly between lineages.…”
Section: Discussionsupporting
confidence: 76%
“…Based on the K2P distance matrix, the COI identification system may help define the limits of nucleotide divergence used to separate lineages (Hebert et al., ). The pairwise genetic distance matrix (Table ) showed considerable divergence between groups, varying from 5.2% to 25.0%, values that are consistent with divergence estimates in studies that have designated new fish species from comparisons with recognized taxa (Amaral et al., ; Baldwin, Cristina, & Lee, ; Bariche et al., ; Connell, Victor, & Randall, ; Guimarães‐Costa et al., ; Melo, Benine, Mariguela, & Oliveira, ; Oliveira et al., ; Tornabene et al., ; Van Tassell, Joyeux, Macieira, & Tornabene, ; Victor, Hanner, Shivji, Hyde, & Caldow, ). When the 2% species threshold for COI sequences (Hebert et al., ) is applied to the data analyzed in the present study, three of the 14 species sampled, Gobiomorus dormitor , Eleotris fusca and Dormitator maculatus , presented evidence of genetic structuring throughout their distribution in the Neotropical and Indo‐Pacific regions, based on nucleotide divergence values of 5.2%–13.1%, as well as reciprocal monophyly between lineages.…”
Section: Discussionsupporting
confidence: 76%
“…and was subsequently barcoded. Its sequence is deposited in BOLD (ACU2979) and GENBANK (KR861539) (see Bariche et al, 2015). Our record constitutes the second confirmed record of this species from Lebanon and the Mediterranean Sea as a whole, 37 years after the first record (see above).…”
Section: Lutjanus Argentimaculatus (Forsskål 1775)mentioning
confidence: 58%
“…In this study, some species were found to be closer to the same species from the eastern Mediterranean Sea. Within this context, it is worth noting that many marine fish species recorded in the Mediterranean Sea have been determined to be alien species of Red Sea origin (Bariche et al ., ), suggesting the possibility of high similarity between The Gulf and Red Sea, even though there is not much fish DNA barcoding data from the Red Sea (Isari et al ., ; Trivedi et al ., ). For what nucleotide composition concerns, results are very similar to those found in Australian (Ward et al ., ), Canadian (Hubert et al ., ), Cuban (Lara et al ., ) and Taiwanese (Bingpeng et al ., ) fish species, with the AT content (53.1%) higher than GC content (46.9%), with the predominance of the T (29.6%).…”
Section: Discussionmentioning
confidence: 99%